Availability assessment of bioenergy and power plant location optimization: A case study for Pakistan. (February 2015) - Biberacher, Markus; Tum, Markus; Günther, Kurt P.; Gadocha, Sabine; Zeil, Peter; Jilani, Rehmatullah; Mansha, Muhammad
Abstract: In terms of land use competition, bioenergy is often subject to controversial discussions. This paper presents a study, which addresses the scope of geographic discrete biomass growth, optimal bio-energy plant locations, and related biomass supply areas. In a first step, annual biomass growth is calculated with the BETHY/DLR model on a spatial resolution of 1 km 2 . In a second step, the ASECO model is utilized to identify optimal plant locations with related biomass supply areas, determined by biomass growth rates and available road infrastructure. The case study is carried out for Pakistan. Scenarios have been investigated on district level, with a special focus on total supply areas for single power plants at identified locations, as well as supply area deviations over the years due to varying biomass growth rates. Achieved results are relevant for the political debate on an optimal bioenergy strategy for Pakistan.